(untitled) (INMR - Innovation & Management Review, 2022)
Purpose – This exploratory research aims to analyze sustainable innovation in the context of inclusive business in Latin America. Design/methodology/approach – The study performs a summative content analysis of 22 inclusive businesses (IBs) of current Business Call to Action (BCtA) members in Latin America. Codes were created to identify the modification or introduction of sustainable products/services/processes. Data were analyzed using NVivo 12. Findings – Results show a prevalence of Colombian examples within Latin American inclusive business, and a more significant proportion in the agricultural sector, consistent with reports found in the literature. The authors found that sustainable innovation takes place when introducing new products/services/processes that respond to the needs of the bottom of the pyramid (BoP) population, or modifying existing processes and services to make them more sustainable. Originality/value – As most sustainable innovation literature is product-oriented and technically dominated, these results contribute to the newer works adopting a more comprehensive conception of innovation, providing empirical evidence at the product, service and process levels. The results provide insights on how inclusive businesses make adaptations to improve the sustainability of their supply chains to bring their products/services within reach of isolated and disadvantaged communities. The findings also suggest that sustainable product innovation in an inclusive business goes beyond a cost reduction objective. Tailored design reveals a hybrid socioeconomic goal with a high degree of local context embeddedness and precise attention to nascent specialized demand. The results could be of practical use for organizations that want to operate an inclusive business in BoP markets.